2011
DOI: 10.1007/s10290-011-0103-0
|View full text |Cite
|
Sign up to set email alerts
|

Expropriation of foreign direct investments: sectoral patterns from 1993 to 2006

Abstract: This paper documents expropriation of foreign direct investment (FDI) across all developing countries for the 1993-2006 period, extending data constructed for earlier decades. This unique data set on worldwide expropriation between 1960 and 2006 is used to highlight several (interrelated) stylized facts. First, although expropriations have become less frequent compared to the 1970s, the number of takings has risen since the mid-1990s. Second, foreign firms are more vulnerable to expropriation in resource-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
86
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(90 citation statements)
references
References 32 publications
2
86
1
1
Order By: Relevance
“…The takeaway from the results is that clarity of responsibility produced by political mandates potentially gives voters more voice in economic policies. 23 The decision by Mexican President Ernesto Zedillo, a US-trained economist, to expropriate a few foreign firms between 1995 and 1998 (Hajzler 2012), at the same time as growing unpopularity with neoliberal policies (e.g., a 1995 Latinobarómetro poll showed that more than 77 percent of the respondents believed that the country was in a bad or very bad economic situation and only 13 percent responded that they expected the situation to get better), and during mid-term elections, also is an example of clarity of responsibility and political mandate at work. Figure A2: Effects of unified government and presidential vote share on expected economic freedom scores (full model).…”
Section: Resultsmentioning
confidence: 99%
“…The takeaway from the results is that clarity of responsibility produced by political mandates potentially gives voters more voice in economic policies. 23 The decision by Mexican President Ernesto Zedillo, a US-trained economist, to expropriate a few foreign firms between 1995 and 1998 (Hajzler 2012), at the same time as growing unpopularity with neoliberal policies (e.g., a 1995 Latinobarómetro poll showed that more than 77 percent of the respondents believed that the country was in a bad or very bad economic situation and only 13 percent responded that they expected the situation to get better), and during mid-term elections, also is an example of clarity of responsibility and political mandate at work. Figure A2: Effects of unified government and presidential vote share on expected economic freedom scores (full model).…”
Section: Resultsmentioning
confidence: 99%
“…They use the term 'natural resource trap' for the privatisation trap in the natural resource context. See also Hajzler (2012) for an overview of sectoral patterns of expropriation.…”
mentioning
confidence: 99%
“…Di Tella, Dubra and MacCulloch (2010) on the interaction between economic conditions on the one hand and social beliefs and political attitudes on the other. 13 Tomz and Wright (2010) present historical evidence for both expropriation and default and show that defaulting states tend also to expropriate. They also analyse how incentives to default and expropriate vary with the economic cycle, risk aversion of governments, and costs of default going back to the seminal paper of Eaton and Gersovits (1981).…”
mentioning
confidence: 99%
“…Three main explanations have been put forward in the literature (Hajzler, 2012). The first one relates to the importance of sunk costs, which is especially clear in resource extracting industries and utilities provision.…”
mentioning
confidence: 99%
“…For example, mineral extraction requires large investments in exploration and not reported separately, and are included in 'Other services'. The number of expropriation acts was collected by Kobrin (1987), Minor (1994 and Hajzler (2012) from reports of expropriations published in a wide range of periodicals. For more details refer to the appendix of Hajzler (2012).…”
mentioning
confidence: 99%